2022
DOI: 10.4103/jfmpc.jfmpc_2518_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of depression, anxiety and stress experienced by health care and allied workers involved in SARS-CoV2 pandemic

Abstract: Introduction: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) causing coronavirus disease 2019 (COVID-19) has led to a global health crisis. Health workforce has been working vigorously in COVID-19 management. So, we have planned this study with an aim to assess the psychological profile of healthcare and allied workers involved in SARS-CoV2 pandemic and to look for associated factors. Methodology: A cross-sectional observational study was planned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…Our participants saw a negative impact of the COVID-19 pandemic across all outcomes (except for resilience scores), similarly to findings from a study in Jordan [50]. A study of healthcare and allied workers involved in the COVID-19 pandemic from India found high levels of severe and extremely severe anxiety (23.2%) and severe and extremely severe depression (11.4%) [54]. The level of severe anxiety was almost double of that found in our study (which did not focus on workers involved in the pandemic).…”
Section: Discussionsupporting
confidence: 79%
“…Our participants saw a negative impact of the COVID-19 pandemic across all outcomes (except for resilience scores), similarly to findings from a study in Jordan [50]. A study of healthcare and allied workers involved in the COVID-19 pandemic from India found high levels of severe and extremely severe anxiety (23.2%) and severe and extremely severe depression (11.4%) [54]. The level of severe anxiety was almost double of that found in our study (which did not focus on workers involved in the pandemic).…”
Section: Discussionsupporting
confidence: 79%
“…15 The findings of the present study are in stark disparity with a similar study conducted in 2020 in AIIMS Patna, where a statistically significant association of depression, stress, and anxiety was found with occupational and marital status. 16 Another study conducted among armed forces doctors reported a significant association of anxiety with age groups (20-35 years) and gender (females). 17 The results of the present study indicated a significant levels of depression, anxiety, and stress among both HCPs and general population; therefore, relevant interventions must be practiced to improve the mental health of people from all quarters during this ongoing pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…As the health care worker is the main force during the Covid-19 era, hence, protecting the nursing workers' psychological health is necessary to control the transmission of coronavirus disease [27]. Thereinto, female health care workers have a higher risk of experiencing depression and anxiety, as female nurses might face different stressors including role pressure, the imbalance between work and life, and lack of enough support [20,28]. In addition, their fear of bringing the coronavirus to family members could also increase the level of anxiety and depression [10,20,21,29].…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…Lack of support, long-term separation from family, no support for mental requirements, and no feedback from doctors, managers, and nurses had increased nurses' anxiety and depression, which infect their psychological health [28]. Hence, Labrague and Santos emphasized the significance of proving adequate organizational support when the level of work stress and anxiety is high [13].…”
Section: Anxiety and Depressionmentioning
confidence: 99%